Dilema Moral Konselor Sekolah: Studi Fenomenologis - Lucky Nindi Riandika Marfu'i; Susi Fitri; Mohamad Saripudin; Nira Prihatin Nufus (Universitas Sebelas Maret, 2026)
Moral dilemmas are often experienced by school counselors because they face complex problems that cause them to experience cognitive dissonance. Counselors' ethical decision-making in dealing with moral dilemmas in schools involves considering the balance between the psychological well-being of students, the principle of confidentiality, and applicable norms, including legal norms. This study aims to analyze the phenomenon of moral dilemmas experienced by school counselors in their work environment through a phenomenological study with thematic data analysis. This study will identify counselors' moral dilemmas which include cases where counselors find it difficult to make decisions, confusion in deciding on counseling services, and decision-making when in difficult positions. Based on the results of the study, the moral dilemmas experienced by schools counselors are categorized into five types of cases namely, the economic condition of the student's family related to the student's activities, the students' intellectual ability condition, parental support for the child's desires, peer conformity, and the stakeholders/others teachers understanding about professional ethics of the school counselor. In addition, school counselors who have been working for more than five years have more complex moral dilemma issues, but ethical decision-making about how to respond and providing guidance and counseling services also to other teachers is more effective and efficient. This phenomenon is a unique issue to be further investigated regarding the ethical decision-making abilities of counselors in schools through specific training.